Single-phase Split-bolus Dual Energy Computed Tomography Angiography for Evaluation of Hemoptysis: A Novel Application. Issue 6 (November 2018) - Meena, Pankaj; Bhalla, Ashu S.; Goyal, Ankur; Sharma, Raju; Kumar, Atin; Srivastva, Deep N.; Sreenivas, Vishnu; Guleria, Randeep
Abstract : Purpose: The purpose of this study was to assess feasibility and overall utility of single-phase split-bolus dual energy computed tomography (DECT) angiography (DECTA) for evaluation of hemoptysis, and to establish an injection protocol for evaluation of hemoptysis, by comparing 2 contrast injection protocols. Materials and Methods: Using dual-source (80 and 140 kV), 2×128-slice equipment, DECTA was performed using 400 mg iodine/mL, 50 to 80 mL iodinated contrast in 257 patients (189 male individuals, 68 female individuals, age range: 15 to 76 y) presenting with hemoptysis. Initially, 50 patients were randomized into 2 groups for 2 different injection protocols (A and B). Images were assessed quantitative and qualitatively. Later, 207 patients were randomized using protocol B, which was technically simpler, and single-CT acquisition, for simultaneous opacification of systemic and pulmonary vessels. Results: Injection protocol A resulted in higher vessel attenuation, both in the aorta and in the pulmonary artery and its segmental branches; however, the difference was not statistically significant. No significant difference was noted in signal-to-noise ratio, contrast-to-noise ratio, as well as subjective image quality parameters. Overall optimal opacification of both systemic and pulmonary arteries was achieved in 247/257 patients. A total of 308 abnormal bronchial arteries were noted. A total of 392 nonbronchial systemic arteries were noted, the majority arising from posterior intercostals and subclavian artery branches. The pulmonary source of hemoptysis was identified in 9 patients (3 pulmonary thromboembolisms, 5 pulmonary artery pseudoaneurysms, and 1 pulmonary venous ectasia). Conclusion: Combined DECTA is a novel technique that enables simultaneous evaluation of both systemic and pulmonary vascular cause of hemoptysis in a single acquisition with small contrast dose. Both injection protocols "A" and "B" were equally efficacious in simultaneous opacification of both the aorta and pulmonary arteries. To the best of our knowledge, such a protocol has never been described for hemoptysis evaluation.